Demand led seed system accelerates adoption of improved bean, sorghum, and groundnut varieties in Tanzania - Mwakatwila, Atupokile; Kimisha, Joseph; Ochieng, Justus; Majambele, Martin; Radegunda, Kessy; Mwanambuu, Daud; Bujiku, Anthony; Alex, Gerald; Madeni, Joachim; Kibaraza, Areth; Rubyogo, Jean Claude; Templer, Noel; et al. (2024)
Producers of Open Pollinated Varieties (OPVs) such as groundnuts, sorghum, and beans primarily source their planting materials from local markets, neighbours, and their own saved seeds, with only 3% obtained from formal or semi-formal seed systems. This heavy reliance on markets and farm-saved seeds has perpetuated the use of outdated varieties that are well-known to traders and farmers. Limited awareness of newer varieties from public seed producers, such as the Tanzania Agricultural Research Institute (TARI), public universities, and private seed companies, has contributed to low adoption rates. As a result, traders and farmers continue to sell and grow old, low-yielding varieties that are susceptible to pests and diseases and are increasingly unable to cope with climate change and other biotic and abiotic stresses. This trend persists due to the low value proposition of new varieties, limited promotional efforts, insufficient data to guide adoption decisions, and a dysfunctional seed supply system developed by the national agricultural research systems